Constructing main/side chain dual-cation poly(mequitazine-terphenyl piperidinium) anion exchange membranes for high-performance fuel cells - Shiyao Sun; Jialin Zhao; Yijia Lei; Jingyi Wu; Jian Gao; Na Li; Jiayao Yang; Jiahao Lu; Liying Yin; Zhe Wang (Materials Reports: Energy)
Anion exchange membranes (AEMs) combining high hydroxide conductivity and alkali-resistant stability have become a major challenge for the long-term development of anion exchange membrane fuel cells (AEMFCs). Here, we designed a series of poly(mequitazine-terphenyl piperidinium) (QPMTP-X) AEMs with dual-functionalized quaternary ammonium cations by introducing a certain proportion of large steric hindrance mequitazine (MEQ) molecular building unit into the poly(aryl piperidinium) backbone. QPMTP-X retains the excellent mechanical properties of the poly(aryl piperidinium), while also combining the alkaline stability and high ionic conductivity exhibited by MEQ with flexible quinuclidinium side chains, achieving an overall improvement of membrane performance. Notably, QPMTP-30 exhibits an ultra-high conductivity of up to 206.83 mS cm−1 and excellent alkaline stability (over 95% conductivity is maintained after 1000 h of conditioning in 2 M NaOH at 80 °C). In fuel cell performance test, QPMTP-30 achieves a peak power density (PPD) of 974.5 mW cm−2 and operates stably at 80 °C for more than 60 h (0.1 A cm−2). Incorporating large steric hindrance building blocks and multi-cations into the poly(aryl piperidinium) backbone not only synergizes the development of high-performance AEMs but also opens up new ideas for the structural design of future AEMs.